Effect Of Different Curing Systems On Strength Characteristics Of Geopolymer Concrete - Naveed Akhtar , S.V. Patankar , S.S. Jamkar , Faizan Ahmed , Saud Mahvi (International Journal of Advanced Science and Technology, 2020)
Geopolymer concrete is a novel development in concrete technology and still it is developing. In the present investigation, effect of different curing systems on compressive strength of fly ash based geopolymer concrete is highlighted. Three system of curing were considered for study by varying fineness and quantity of fly ash. Two types of low calcium processed flyash were taken from thermal power plant of fineness 600m2/kg and 400m2/kg. Ten geopolymer mixes were prepared and tested for compressive strength using cubes of size 100x100x100 mm. The systems of curing are hot air oven curing, solar oven curing and atmospheric curing. The results shows enhanced compressive strength by solar oven curing as compare to atmospheric temperature curing of geopolymer concrete. Similarly, there is no large variation in compressive strength of geopolymer concrete using Electric oven curing and solar oven curing for fineness of FA 400m²/kg.